Letramentos acadêmicos em contextos internacionais: reflexões sobre a experiência acadêmica mediada por uma língua estrangeira - Morgana Rodrigues da Silva Santos de Oliveira (2018)
This study analyzes the experience of university students with literacy practices of higher education institutions in different countries. The choice to investigate the academic experience of exchange students was focused on the possible challenges that this context may offer, especially because students need to use a foreign language to mediate all their academic production in another country. Accordingly, the research was developed to answer two main questions: how exchange university students reflect on the demands of academic life by contrasting their study experience at their home university and that at the destination university in another country? What was the role of the foreign language in the academic life and production of international students? Therefore, this study draws on academic literacys theoretical assumptions (LEA; STREET, 1998, LILLIS, 1999, GEE, 2010, FIAD, 2016, LEA, 2017) and on the vision of reading and writing as social practices (STREET 1984, 1993, 2003, 2007, 2017; STREET, 2007; GEE, 2010; STREET; CASTANHEIRA, 2014; STREET; May, 2017). With these guiding theorizations, the research was developed from a qualitative approach (LÜDKE; ANDRE, 1986; FLICK, 2009), made possible by semi-structured interviews (MARCONI; LAKATOS, 2010, 2011) with six undergraduate students participating in the UFMGs Minas Mundi Program in the year 2016. The interviews transcripts were analyzed through the exploration of some analytical procedures of content analysis, proposed by BARDIN (2011). The data analysis evidenced several nuances of the academic experience lived by the interviewees in the different academic contexts in which they were introduced. Among these nuances, we highlight the norms and conventions for communication and the meanings of literate actions in different university contexts. The data analysis also made it possible to highlight the reflective and agentive character of the exchange students as they revisited their study experience in an international context and as they identified challenges and formulated strategies to deal with the discursive formality of the academic community and had to deal with written and oral communication in a new language. As for academic production, students encountered challenges with writing in a foreign language, which required them to take more time to study and adopt strategies to deal with the demands of written production. As they navigated across different disciplinary areas and academic contexts, the students have read many texts and as a result, they have found many technical terms within those texts. They have adopted strategies to assist them in understanding these terms, using the texts themselves to contextualize their meanings. Regarding oral genres, students had a double challenge: to deal with the formalities and specificities of the academic community and, at the same time, to orient themselves through a foreign language for communication in that context. The social aspect of learning seems to become more evident in the international academic context, as evidenced in their reflections during the interviews, as students engage in groups and participate in interactions, they observe how people communicate, behave and assimilate cultural nuances, adapting the uses of the language for their needs in the day to day life of the academic life.